STRATEGI DINAS KETENAGAKERJAAN DALAM MENGURANGI ANGKA PENGANGGURAN DI KABUPATEN BANDUNG JAWA BARAT - Salim Sungkar , Fatimah; Mahendra, Medi; Abdul Rozak Riaji, Isnandi (STISIP Widyapuri Mandiri, 2025)
This research aims to analyze the strategies implemented by the Employment Agency of Bandung Regency in reducing the unemployment rate. Using Kootten's strategy theory, this study examines the effectiveness of organizational strategies, program strategies, resource support strategies, and institutional strategies implemented by the agency. The results show that the program strategy has been running well through the implementation of activities such as job fairs and job vacancy announcements that are in accordance with community needs. However, the resource support strategy is considered inefficient due to the less-than-optimal utilization of resources, caused by limited competent manpower, infrastructure facilities, and inadequate funding. Meanwhile, institutional strategies have been running quite well with programs designed according to needs and planned, although some programs are still not implemented optimally. Based on these findings, it is recommended that the Manpower Office increase the capacity of human resources, improve infrastructure, and optimize funding to support the effectiveness of the strategies implemented to reduce unemployment in Bandung Regency.